E-learning During COVID-19 in a Medical College - Almuzaini, MD, Hanan I. (International Journal of Innovative Research in Medical Science, 2021)
Recently, many medical schools shifted from live lectures to online lecture by reducing classic lectures with using more technology. E-learning increased all over the world during the period of the spread of the COVID-19 virus. In addition, it is important to know if such learning strategies are advantageous. This will help institutions consider how to distribute their funding resources for platform design and online learning.